Early intervention for children with intellectual and developmental disability using drama therapy techniques. (February 2020) - Wu, Jiaojiao; Chen, Keqin; Ma, Ying; Vomočilová, Jana
Abstract: A total of 30 sessions of group drama therapy were carried out regularly for 10 homeless children aged 3–6 years old with mild to severe intellectual and developmental disability to examine the effectiveness of drama therapy techniques in early intervention. Universal drama therapy approaches included sensory play, body games, sounds, stories, role playing, improvisation by embedding techniques within dramatic activities and working with multifarious materials. By conducting questionnaire survey, researchers collected responses of the observers who witnessed the sessions in field. Research findings from progress monitoring indicated child participants concentrated on the process of group drama therapy and spontaneously participated in peer interaction. Child participants increased and maintained their rates of communication and cooperation during intervention and afterwards. Some other dimensions, including creativity, flexibility, imagination and using social skills also increased. Children were perceived as happy in group drama therapy activities accompanied by self-exploration and getting to know others.